Prospects for agricultural development in rural territories. Project of The World Bank "Promoting business development in agricultural holding" (EBA) - Avramchuk, B.; Loshakova, Y. (Land Management, Cadastre and Land Monitoring, 2019)
(EBA) is an initiative of the World Bank Group, which defines and controls policy rules which affect agricultural and agribusiness markets. The project presents globally comparable nature of data that can inform the government about decision-making processes and encourage it to conduct policy dialogues with stakeholders to create a facilitate environment for local, regional and international business in agriculture.The project "Promoting business development in agricultural holding 2017" aims to assist creation of more favorable conditions for agricultural business. By providing the key information about regulatory documents whic hare compared at the global level, the project builds a data base that can be used to start a dialogue about policy and reforms development. These challenges can stimulate activities of a private sector and lead to create more efficient and effective chains of values in agriculture economy.Key words: GDP, agribusiness, strategy, globalization, urbanization